2012
DOI: 10.1177/0278364912464669
|View full text |Cite
|
Sign up to set email alerts
|

Motion control of magnetized Tetrahymena pyriformis cells by a magnetic field with Model Predictive Control

Abstract: This paper presents the Model Predictive Control (MPC) of magnetized Tetrahymena pyriformis (T. pyriformis) using a magnetic field. The magnetized T. pyriformis are generated by feeding spherical iron oxide particles into the cells. Using an external magnetic field, we change the movement direction of the cell, but the speed of the cell remains constant regardless of the strength of the external magnetic field. The contributions of this paper are threefold. First, the discrete-time plant model of the magnetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In this context, sophisticated and advanced control algorithms, based especially on a model-based predictive control, have been demonstrated to enable very accurate autonomous navigation of magnetic microrobots [47]- [49]. Ou et al, for example, developed a predictive control of magnetized Tetrahymena pyriformis for changing the orientation of the cell, whereas the speed of the cell remained constant regardless of the strength of the external magnetic field [48]. Making a comparison with more classic PID feedback control, although the model predictive control algorithms bring advantages in terms of time delays, accuracy, and high-order dynamics, they need a long time to solve optimization problems due to hardware limitations in the high-computational cost.…”
Section: Navigation Of Magnetic Microrobots With Different User Intermentioning
confidence: 99%
“…In this context, sophisticated and advanced control algorithms, based especially on a model-based predictive control, have been demonstrated to enable very accurate autonomous navigation of magnetic microrobots [47]- [49]. Ou et al, for example, developed a predictive control of magnetized Tetrahymena pyriformis for changing the orientation of the cell, whereas the speed of the cell remained constant regardless of the strength of the external magnetic field [48]. Making a comparison with more classic PID feedback control, although the model predictive control algorithms bring advantages in terms of time delays, accuracy, and high-order dynamics, they need a long time to solve optimization problems due to hardware limitations in the high-computational cost.…”
Section: Navigation Of Magnetic Microrobots With Different User Intermentioning
confidence: 99%
“…We record the discrete-time cell orientation information as 0 4 (Ο), 0<(1),..., O^k),..., 0 4 (π), and the magnetic field orientation as ψ(0), ψ(1), · · ·, i>(k), ... ,ψ(η). The following equation is derived from (9).…”
Section: B System Identificationmentioning
confidence: 99%
“…Y. Ou Using two sets of orthogonal electromagnets (left), Ou et al demonstrated steering a living magnetized T. pyriformis cell [9](middle). In this paper we exploit differences in magnetism between cells to steer multiple cells to arbitrary x, y locations and stabilize them in limit cycles at these locations (six stabilized cells shown at right).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [9] use realtime feedback control and the Rapidly-exploring Random Tree (RRT) for path planning to control the movement of magnetotactic T. pyriformis as micro-robots. Ou et al [10] investigate the motion control of T. pyriformis cells using the Model Predictive Control (MPC) algorithm. These control Fig.…”
Section: Introductionmentioning
confidence: 99%